2022
DOI: 10.1101/2022.01.05.22268782
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Protection afforded by prior infection against SARS-CoV-2 reinfection with the Omicron variant

Abstract: BACKGROUND: Natural SARS-CoV-2 infection elicits strong protection against reinfection with the Alpha (B.1.1.7), Beta (B.1.351), and Delta (B.1.617.2) variants. However, the Omicron (B.1.1.529) variant harbors multiple mutations that can mediate immune evasion. We estimated effectiveness of prior infection in preventing reinfection (PES) with Omicron and other SARS-CoV-2 variants in Qatar. METHODS: PES was estimated using the test-negative, case-control study design, employing a methodology that was recently i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 25 publications
3
43
0
1
Order By: Relevance
“…This contrasts with what we observed in a previous analysis, where we did not find an increased risk of infection with the Delta, Beta (B.1.351) and Gamma (P.1) variants vs the Alpha variant in previously infected individuals [ 21 ]. Our finding of reduced protection against reinfection with Omicron is in line with reports showing increased risk of reinfections with the Omicron variant [ 22 - 24 ].…”
Section: Discussionsupporting
confidence: 92%
“…This contrasts with what we observed in a previous analysis, where we did not find an increased risk of infection with the Delta, Beta (B.1.351) and Gamma (P.1) variants vs the Alpha variant in previously infected individuals [ 21 ]. Our finding of reduced protection against reinfection with Omicron is in line with reports showing increased risk of reinfections with the Omicron variant [ 22 - 24 ].…”
Section: Discussionsupporting
confidence: 92%
“…We show that prior SARS-CoV-2 infection prevented symptomatic reinfection with Omicron at 45%-60%, what is consistent with results from a large population study in Qatar [7]. Although it has been suggested that Omicron is evasive to neutralizing antibodies induced by natural infection from previous variants or vaccine-elicited[8], we show that HCW who were not infected by Omicron during the five week period of this analysis had higher concentration of anti-spike IgG prior the symptomatic visit, with >1549BAU/mL being the threshold suggestive of significant reduction in the risk of symptomatic Omicron infection.…”
Section: Discussionsupporting
confidence: 90%
“…We have quantified two aspects of comparative severity of Omicron vs. Delta variant infections: the risk of progression to severe endpoints among diagnosed cases, and the risk of progression to acute respiratory symptoms among those first diagnosed before symptoms onset. While attenuation of disease severity in association with the Omicron variant is an encouraging finding, prior evidence of higher transmissibility of Omicron variant infections [27], as well as immune evasion from prior infection [28] and vaccination [68], are concerning. Rapid spread of the Omicron variant in a compressed time period has led to unprecedented surges in COVID-19 among our study population and others globally.…”
Section: Discussionmentioning
confidence: 99%